The Recreation and Leisure Pursuits of Employed Adults with Visual Impairments in Nigeria: Part 2. (January 2015) - Ajuwon, Paul M.; Kelly, Stacy M.; Wolffe, Karen E.
Introduction: Indoor and outdoor activities play an important role in enhancing the health and well-being of people with and without disabilities in developed countries. The status of recreational activities, however, is not a priority in many developing countries—those in which people struggle daily to eke out a living. This study investigates the recreation and leisure experiences of employed adults with visual impairments (those who are blind or have low vision) who live and work in Nigeria—one of the world's most populous developing nations. Methods: We developed a questionnaire that assessed recreation and leisure among a sample of 172 adults with visual impairments living and working in Nigeria. Statistical analysis procedures included descriptive and nonparametric methods. The Mann-Whitney U- test compared the difference between the mean ranks of five recreational experience measures (dependent variables) within the independent groups. Results: Gender, degree of visual impairment, age at onset of visual impairment, educational attainment, annual income, and postsecondary education were all characteristics that evidenced significant differences ( p < .05) in the participants' recreation and leisure experiences that were evaluated. Discussion: Male respondents with visual impairments and those with higher earning power were engaged more often in recreation and leisure than were female respondents or those with less robust financial situations. Furthermore, recreational activities were most important to quality of life for respondents who had at least one postsecondary degree. Individuals with low vision reported higher levels of satisfaction than those who are blind. Implications for practitioners: It is imperative for stakeholders to explore opportunities that will increase the level of participation in recreation of people with visual impairments of both genders and all degrees of financial earning power in developing nations. The value of postsecondary education is underscored.